Representasi Bentuk Cinta Tokoh Fang Yuke dalam Film Love The Way You Are - Widyastira JP, Sania; Putri, Dinda Anindya; Rudiansyah, Rudiansyah (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2021)
This research discusses the representation of the form of love on the male main character in the film which is a China film released on June, 21 2019. The purpose of this research is to describe the representation of the form of love on the male main character. This research is based on using Sternberg’s theory of love and Charles Sanders Pierce’s semiotic theory which is only using sign theory to understand the form of love on male main character. The research method used is qualitative descriptive research. Based on the analysis of the love the way you are film, researcher found 3 (three) components of Sternberg’s love. Thus, it can be concluded Fang Yuke is proven to show a form of love between himself and the woman character he loved. Keywords: literature, love the way you are, representation, love